ANALISIS SEGMEN PASAR WISATAWAN KELUARGA DI SAUNG ELING, KOTA BOGOR - Akib Hehanussa; Shandra Rama Panji Wulung; Mohamad Dwi Sapari Hadian; Ayu Krisnha Yuliawati (Fakultas Pariwisata Universitas Pancasila, 2022)
This study aims to analyze the phenomenon of family tourism and to identify the strategies carried out by the Saung Eling manager in dealing with the family tourist market segment. Saung Eling is located in Kampung Lembur Sawah, Kelurahan Mulyaharja, Bogor City. The research method used is a qualitative research method with a phenomenological analysis approach. The information collection technique used are interviews, observations, and documentation of the tourist area, managers, and workers of Saung Eling. Results of the research shows that there is a family tourist phenomenon in the Saung Eling. This is proven by the increase number of family tourist visits to Saung Eling, as well as the number of revisit intentions of more than 10 times by family tourists. In addition, the strategies carried out by the manager of Saung Eling are; in terms of accessibility, the manager of Saung Eling makes it easier for tourists by directly picking up tour groups at points that are easily accessible to tourists. There are directions to Saung Eling also placed at several crossroads. In terms of attractions, Saung Eling provides two main attractions, namely culinary tourism and nature tourism. Culinary at Saung Eling also features local specialties, such as pala squash and nasi liwetan. Meanwhile, nature tourism is packaged in the form of tour packages around the village by utilizing a beautiful rural atmosphere and local wisdom that still emphasizes Sundanese culture. Apart from tour packages. Saung Eling also provides supporting facilities such as parking lots, CHSE, prayer rooms, toilets, and homestays (both in the house that has been prepared as a homestay or at the Saung Eling homestay).